Synthesis and Crystal Structure of 1-(2-Fluorophenyl)-3-(1H-1,2,4-triazol-1-yl)propan-1-one - Zeng, Wulan; Wang, Lintong; Guo, Huanmei; Jian, Fangfang (Asian Journal of Chemistry, 2010)
The compound 1-(2-fluorophenyl)-3-(1 H-1,2,4-triazol-1-yl)propan-1-one, was synthesized and characterized by means of elemental analysis, IR spectrum and X-ray diffraction. It crystallizes in monoclinic, space group P2(1)/c with a = 11.757(15), b = 4.904(6), c = 21.50(3) Å, b =118.11(6)º, C11H10N3OF, Mr = 219.21, V = 1093(2)Å3, Z = 4, Dc = 1.326 g/cm3, F(000) = 452, μ= 0.101 mm-1, final R1 = 0.1101. The triazole ring and 2-fluorophenyl ring makes dihedral angles of 85.97º. There is obvious potentially weak intra- and intermolecular C-H···O hydrogen bonds in the crystal, which stabilizes the crystal structure.